Meningkatkan Kemampuan Kosakata Anak Usia 4-5 Tahun melalui Media Wayang Papercraft di TK Merpati Simpang Sungai Rengas - Sinta Nia Meylinda; Uswatul Hasni; Haryanto Haryanto (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Early childhood (0–6 years) is a critical period in human development, often referred to as the golden age, during which all aspects of development, including language and vocabulary, grow rapidly. However, based on preliminary observations at TK Merpati, Simpang Sungai Rengas District, the vocabulary skills of children aged 4–5 years were still relatively low. This study aimed to examine the effectiveness of papercraft puppet media in improving the vocabulary skills of children aged 4–5 years at TK Merpati, Simpang Sungai Rengas District. The research employed a classroom action research design conducted in three cycles. The subjects consisted of 17 children aged 4–5 years. Data were collected through observation sheets, and data analysis was carried out by comparing the percentage of children’s vocabulary achievement before and after the implementation of the papercraft puppet media in each cycle. The results indicated a significant improvement in children’s vocabulary skills. In the pre-action stage, children’s achievement was categorized as Not Yet Developed (NYD) with a percentage of 30%. In Cycle I, the percentage increased to 50% (Beginning to Develop). In Cycle II, it further improved to 76% (Developed as Expected). In Cycle III, the results reached 95% (Very Well Developed). These findings demonstrate that papercraft puppet media is effective in enhancing vocabulary development in early childhood.